The Effectiveness of Spiritually Multidimensional Psychotherapy (SMP) on Psychological Capital and Stress Symptoms of Patients with Type 2 Diabetes - Rafiee Shafigh, Mitra; Rajaei, Alireza; Janbozorgi, Masoud (International Journal of Applied Behavioral Sciences, 2021)
Background and Aim:Psychological stress often raises blood sugar levels in people with type 2 diabetes. Psychological capital has a protective role and leads tothe healthy state of individuals.The current study aimed to investigate the effect of spiritually multidimensional psychotherapy (SMP) group training on psychological capitaland stress symptoms in type 2 diabetic patients. Materials and Methods:The research was semi-experimental research with a control group. The statistical population consisted of all patients with diabetes covered by the Mashhad Diabetes Foundation. From this group, 60 people were selected by network method or snowball and were randomly divided into two groups (experimental and control). The experimental group received spiritually multidimensional psychotherapy group training in 12 sessions of 90 minutes weekly. Before and after the intervention, a stress symptoms questionnaire and psychological capital were performed in both experimental and control groups. Data analysis was performed using univariate and multivariate covariance using SPSS.21 software. Results:The findings revealed that spiritually multidimensional psychotherapy (SMP) had a significant effect on psychological capital (P<0.001) and stress symptoms (P<0.001). Likewise, this effect on the components of self-efficacy, hope, resilience, and optimism was significant (P<0.001). Conclusion:It can be concluded that spiritually multidimensional psychotherapy training can increase psychological capital and decrease stress symptoms in patients with type 2 diabetes.